Plant-environment interactions - Wilkinson, R. E. 1926- (Marcel Dekker, 2000)
Presenting comprehensive coverage of differentiated plant responses to changing environments, this volume focuses upon how multiple and combined stress factors influence plant survival. It has been updated for the second edition and features over 1500 new citations.
Keywords: Plant ecophysiology.; elektronické knihy; electronic books